2015
DOI: 10.1080/10508414.2015.1162639
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mindfulness Training on Physiological Measures of Stress and Objective Measures of Attention Control in a Military Helicopter Unit

Abstract: Objective: This study sought to determine if mindfulness training (MT) has a measurable impact on stress and attentional control as measured by objective physiological and psychological means. Background: Periods of persistent, intensive work demands are known to compromise recovery and attentional capacity. The effects of 4-month MT on salivary cortisol and performance on 2 computer-based cognitive tasks were tested on a military helicopter unit exposed to a prolonged period of high workload. Methods: MT part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 52 publications
3
28
1
1
Order By: Relevance
“…The findings were consistent with previous research (see Mantzios, 2014;Färber & Rosendahl, 2018) suggesting that poor mental health can affect resiliency, and therefore overall wellbeing. The present findings build on existing evidence of other research that looked into the benefit of mindfulness and self-compassion (e.g., Baer et al, 2012;Brewer, 2014;Meland et al, 2015). It is fair to assume that identifying these psychological traits (i.e., mindfulness and self-compassion) as potentially enhancing mental health and resiliency may mediate further health behaviours (e.g., smoking, addiction and eating impulsively) (Egan, Mantzios, & Jackson, 2017;Egan & Mantzios, 2018).…”
Section: Resultssupporting
confidence: 82%
“…The findings were consistent with previous research (see Mantzios, 2014;Färber & Rosendahl, 2018) suggesting that poor mental health can affect resiliency, and therefore overall wellbeing. The present findings build on existing evidence of other research that looked into the benefit of mindfulness and self-compassion (e.g., Baer et al, 2012;Brewer, 2014;Meland et al, 2015). It is fair to assume that identifying these psychological traits (i.e., mindfulness and self-compassion) as potentially enhancing mental health and resiliency may mediate further health behaviours (e.g., smoking, addiction and eating impulsively) (Egan, Mantzios, & Jackson, 2017;Egan & Mantzios, 2018).…”
Section: Resultssupporting
confidence: 82%
“…Similar to the Stroop task literature, there is mixed evidence for improvements following mindfulness training on these tasks. Non-randomized studies have yielded evidence for increased accuracy and RT on the SART following 7 weeks of mindfulness training (Morrison, Goolsarran, Rogers, & Jha, 2013) and MBSR (Meland et al, 2015) compared to wait-list controls. In pre-deployment military personnel, those who engaged in high amounts of mindfulness practice time exhibited greater sensitivity on this task and reduced self-reported mindwandering than those with low practice time (Jha et al, 2017).…”
Section: Mindfulness Training and Measures Of Top-down Attentionmentioning
confidence: 99%
“…In contrast to these favorable results, there is also evidence that mindfulness training fails to impact other facets of bottom-up attention. One feasibility study found no differential improvements on a stimulus-driven attentional capture task following MBSR compared to a wait-list group (Meland et al, 2015). An RCT examining performance on an anti-saccade task, requiring participants to inhibit a reflexive saccade towards a peripheral stimulus and instead execute a voluntary saccade in the opposite direction, found no differential impact of mindfulness training compared to N-back training or combined training (Course-Choi et al, 2017).…”
Section: Mindfulness Training and Measures Of Bottom-up Attentionmentioning
confidence: 99%
“…MT has been offered in many real-world contexts (Good et al 2015), and one setting where it has shown promise is with active-duty military personnel (e.g., Bijlsma et al 2019;Jha et al 2010;Johnson et al 2014;Meland et al 2015). The motivation for providing MT to military service members stems, in part, from prior research showing decline in cognitive performance over high-demand intervals, such as survival school training (Morgan et al 2006), and stress inoculation training (Lieberman et al 2005).…”
mentioning
confidence: 99%